2019
DOI: 10.1016/j.jebo.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effect on European adolescents’ social network

Abstract: We contribute to the literature on relative age effects on pupils' (non-cognitive) skills formation by studying students' social network. We investigate data on European adolescents from the Health Behaviour in School Aged Children survey and use an instrumental variables approach to account for endogeneity of relative age while controlling for confounders, namely absolute age, season-of-birth, and family socioeconomic status. We find robust evidence that suggests the existence of a substitution effect: the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…In addition, relative youth has been associated with poorer peer relationships, which might result in an increased incidence of depression. 11,12 Other potential explanations for the association between relative age and depression include the possibility that length of time in school (greater at any given age for relatively young children) may be associated with depression. A seasonal association between month of birth and depression cannot be ruled out.…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, relative youth has been associated with poorer peer relationships, which might result in an increased incidence of depression. 11,12 Other potential explanations for the association between relative age and depression include the possibility that length of time in school (greater at any given age for relatively young children) may be associated with depression. A seasonal association between month of birth and depression cannot be ruled out.…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…8 Younger relative age has also been associated with lower self-esteem, reduced confidence in abilities, peer problems, and increased internalizing symptoms. [9][10][11][12] One potential consequence of these differences may be an increased risk of depression. Although studies from Canada and Japan have identified an association between young relative age and increased risk of suicide, these investigations did not directly investigate the association between relative age and diagnosis of depression.…”
mentioning
confidence: 99%
“…the date that determines the 'academic year' or the grade 1 to which the student is assigned). Relative age is mirrored by maturity differences and, in turn, by gaps in students' performance and (non)cognitive abilities (Fumarco & Schultze, 2019;Fumarco & Baert, 2019;Peña, 2017;Schwandt & Wuppermann, 2016;Patalay et al, 2015;Ponzo & Scoppa, 2014;Black et al, 2011;Mühlenweg et al, 2012;Dhuey & Lipscomb, 2010;Sprietsma, 2010;Mühlenweg, 2010;Elder & Lubotsky, 2009;Dhuey & Lipscomb, 2008;Bedard & Dhuey, 2006;Lien et al, 2005;Allen & Barnsley, 1993). These gaps are also known as 'relative age effects' (RAEs), and it is legitimate to expect that, in any class of students, they are reflected by the younger students' lower well-being.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some evidence that these gaps continue and shape success in adulthood (Gladwell, 2008). Indeed, some studies have investigated the effect of relative age, while controlling for absolute age, on social network (Fumarco & Baert, 2019), on grit and other character skills (Peña & Duckworth, 2018), and on performance (Ponzo & Scoppa, 2014). Other studies have found relative age effects on performance in different age groups (Nam, 2014;Allen & Barnsley, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This age difference can matter. The relatively older students (born soon after the cutoff date) enjoy better performance, (non)cognitive abilities, and well-being than relatively younger students, who are born just before the cutoff (Fumarco & Baert, 2019Navarro et al, 2015;Bernardi, 2014;Ponzo & Scoppa, 2014;Sprietsma, 2010;Dhuey & Lipscomb, 2010;Cobley et al, 2009;Dhuey & Lipscomb, 2008;Bedard & Dhuey, 2006;Thompson et al, 2004). These disparities are also known as relative age effects (RAEs) (see Barnsley & Thompson, 1988).…”
Section: Introductionmentioning
confidence: 99%